2015
DOI: 10.4103/2008-7802.153860
|View full text |Cite
|
Sign up to set email alerts
|

Trend and pattern of various types of cancer with special reference to gall bladder cancer in North Bengal medical college, West Bengal, India: A 3 years record based study

Abstract: Background:Global burden of cancer is on rise and trends and pattern of cancers are rapidly changing different geographic and population groups. Gall bladder cancers are emerging with increasing proportion among select areas and groups and understanding these variations are important for appropriate strategies and interventions. However, absence of a well-developed universal cancer registry system in India, institution based secondary data analysis can generate useful information. The present study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…11 Study reveals Blue-Green-Red mosaic pattern on sonoelastography indicate non-malignant cystic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Study reveals Blue-Green-Red mosaic pattern on sonoelastography indicate non-malignant cystic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Study done by Ghosh et al, 2015 showed increase in incidence of breast cancer in females of West Bengal. 9 According to the PBCR of 2012-14 similar incidence of increase breast cancer has been found in other cities of the country, like Delhi, Bangalore, Chennai, Manipur, Kolkata and Mumbai. 10 Breast cancer is common in affluent societies having a western lifestyle.…”
Section: Discussionmentioning
confidence: 86%
“…It has a varying demographic distribution in different parts of the world as well as in our country. It is a common cancer in the Ganges belt of North Eastern India and is due to high concentrations of heavy metals in water and soil of villages along the Indo-gangetic plains (5). Its incidence in this region is one of the highest in the world.…”
Section: Resultsmentioning
confidence: 99%